Solve for m 4m=6m-4

Math
4m=6m-4
Move all terms containing m to the left side of the equation.
Tap for more steps…
Subtract 6m from both sides of the equation.
4m-6m=-4
Subtract 6m from 4m.
-2m=-4
-2m=-4
Divide each term by -2 and simplify.
Tap for more steps…
Divide each term in -2m=-4 by -2.
-2m-2=-4-2
Cancel the common factor of -2.
Tap for more steps…
Cancel the common factor.
-2m-2=-4-2
Divide m by 1.
m=-4-2
m=-4-2
Divide -4 by -2.
m=2
m=2
Solve for m 4m=6m-4

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top